Zeolite based ethylbenzene production modeling; Chemical Reactors (CHEMREACTOR-22) - Khlebnikova E. S. Elena Sergeevna; Ivashkina E. N. Elena Nikolaevna; Ignatova L. S. Lyubov Sergeevna; Koshkin S. A. Stanislav Aleksandrovich (2016, 2016)
Title screen